Bibliometrik Analysis of Self Care in Patient with Type 2 Diabetes Mellitus - Murni, Weny; Ernawati (Babali Nursing Research, 2025)
IntroductionType 2 Diabetes Mellitus is a chronic metabolic disorder with a high global prevalence and a significant risk of complications. The management of this condition heavily relies on effective self-care practices. However, many patients face challenges in implementing self-care due to limited knowledge, inadequate skills, and insufficient social support. The study aimed to employ a Bibliometric analysis to provide a comprehensive overview of the scientific development related to self-care behaviors among patients with Type 2 Diabetes Mellitus. Methods: This study employed a quantitative descriptive method with a bibliometric approach, analyzing scientific publications retrieved from the Scopus database for the period 2021–2025. The search keywords (TITLE-ABS-KEY: "self-care" AND "patient" AND "type 2 diabetes mellitus") yielded 55 articles, which were analyzed using VOSviewer software to map keyword co-occurrence patterns, topic density, and publication trends. Results: The network visualization revealed 179 terms grouped into nine thematic clusters, with dominant terms such as “patient,” “self-care,” “intervention,” and “self-efficacy.” The overlay visualization indicated a shift from conventional educational approaches toward using digital technologies and psychosocial strategies (e.g., smartphone applications, motivation, and self-regulation models). The density visualization identified underexplored areas such as rural contexts, digital technology, and behavior-based approaches, highlighting opportunities for innovative research. Conclusion: This study demonstrates that the topic of self-care in patients with Type 2 Diabetes Mellitus is rapidly evolving, with a growing trend toward interdisciplinary approaches and personalized care. Future research is recommended to explore digital health technologies, psychosocial models, and interventions tailored to the patients' cultural and social contexts